Phenotypes of Bacillus subtilis mutants lacking multiple class A high-molecular-weight penicillin-binding proteins. - Popham, D L (1996)
Examination of Bacillus subtilis strains containing multiple mutations affecting the class A high-molecular-weight penicillin-binding proteins (PBPs) 1, 2c, and 4 revealed a significant degree of redundancy in the functions of these three proteins. In rich media, loss of PBPs 2c and 4 resulted in no obvious phenotype. The slight growth and cell morphology defects associated with loss of PBP 1 were exacerbated by the additional loss of PBP 4 but not PBP 2c. Loss of all three of these PBPs slowed growth even further. In minimal medium, loss of PBPs 2c and 4 resulted in a slight growth defect. The decrease in growth rate caused by loss of PBP 1 was accentuated slightly by loss of PBP 2c and greatly by loss of PBP 4. Again, a lack of all three of these PBPs resulted in the slowest growth. Loss of PBP 1 resulted in a 22% reduction in the cell radius. Cultures of a strain lacking PBP 1 also contained some cells that were significantly longer than those produced by the wild type, and some of the rod-shaped cells appeared slightly bent. The additional loss of PBP 4 increased the number of longer cells in the culture. Slow growth caused by a mutation in prfA, a gene found in an operon with the gene encoding PBP 1, was unaffected by the additional loss of PBPs 2c and 4, whereas loss of both prfA and PBP 1 resulted in extremely slow growth and the production of highly bent cells.